Language practice and policy in Israeli hospitals: the case of the Hebrew and Arabic languages - Yael Keshet; Ariela Popper-Giveon (BMC, 2019)
Abstract Background Organizational language practice and policy are not neutral elements but reflect social and political power relations. The micro-level of working groups is subject to the influence of political conflicts and power relations at the macro-level. In conflict zones in particular, these involve complex considerations. Consequently, the present research sought to examine tensions arising from the language spoken among mixed Jewish-Arab teams in Israeli public hospitals. Methods In-depth interviews were conducted during 2016-2017, with 50 Jewish and Arab healthcare practitioners - 10 managers, 20 physicians, and 20 nurses - employed in 11 public hospitals in Israel. Results Our interviews with healthcare practitioners revealed that speaking Arabic in the presence of the patient (not with the patient) may evoke negative feelings and resentment among both Jewish patients and colleagues. Moreover, conflicting attitudes may come into play when Arab practitioners speak Arabic among themselves. Two contexts of language use in Israeli public hospitals can be noticed: the language used in the presence of the patient; and the language used among the practitioners when no patient is present. The former involves the principles of cultural and linguistic competency, and is therefore governed by clear guidelines and procedures. The latter echoes the tensions between the two ethno-national groups in Israel, Jews and Arabs, and is not regulated by a clear policy formulated by the Ministry of Health or by the hospitals' managements. Conclusions Our analysis of language practice and policy as a multi-leveled phenomenon, where the micro-level of everyday interactions is influenced by the macro-level of political life, indicates a need for meso-level policy, led by the Ministry of Health. A policy of linguistic competency should be publicized and enforced to ensure that in the presence of the patient, practitioners speak a language s/he understands. This policy should also stipulate that among mixed teams of healthcare professionals every language is permissible, while the language spoken in a particular context should be understood by everyone present.